2D weight functions of stress intensity factors for high aspect ratio semi-elliptical surface cracks in finite thickness plate. (December 2020) - Yuan, Kuilin; Jiang, Yan; Liu, Jiayun; Hong, Ming
Highlights: 2D weight functions were proposed for high aspect ratio semi-elliptical surface cracks in finite thickness plate. Parametric 3D finite element calculations were performed to develop the weight functions. The proposed 2D weight functions could be applied to a wide range of deep surface crack shapes. Acceptable accuracy for the SIFs estimation. Abstract: This paper presents the application of the weight function method for calculating the stress intensity factors for high aspect ratio semi-elliptical surface cracks in finite thickness plate subjected to arbitrary two-dimensional stress fields. Based on the formulation initially proposed by Wang and Glinka (2009), an extended 2D weight function for surface cracks with aspect ratio 1.0 ≤  a / c  ≤ 8.0 is developed. The unknown coefficients in the formulation can be determined from reference stress intensity factors which are obtained by finite element analysis with the J-integral method. The effectiveness of the proposed weight functions have been verified by comparing the stress intensity factors available in the literatures and those obtained from FEM for several linear and nonlinear two-dimensional stress distributions, indicating a good accuracy. The present results complement the application range of 2D weight functions for low-aspect-ratio cracks, 0.0 <  a / c  ≤ 1.0, developed by the previous researchers.